Türkiye’s Inclusive Growth Performance - Abuk Duygulu, Aylin; Keskin, Nagehan (International Journal of Contemporary Economics and Administrative Sciences, 2024)
This study examines the inclusiveness of economic growth in Türkiye during the post-2000 period through an analysis of the indicators used in constructing the Inclusive Growth Index (IGI) developed by United Nations Conference on Trade and Development (UNCTAD). To ascertain the extent to which economic growth is inclusive, the performance of Türkiye for each UNCTAD IGI indicator is evaluated by comparing it with the averages of Upper Middle-Income Countries (UMICs) and Organisation for economic Co-operation and Development (OECD) countries. The analysis results indicate that in terms of achieving inclusive growth, Türkiye's performance in indicators related to living conditions is positive, while its performance in indicators related to economy, equality, and environment is inadequate. Particularly, Türkiye's performance in equality-related indicators lags far behind the UMIC and OECD averages, suggesting a continuous and rapid need for improvement in this area. The existence of comprehensive reports and action plans prepared by public institutions in Türkiye covering almost all dimensions of inclusive growth demonstrates that policymakers are not lacking in analyzing the current situation and identifying necessary actions. However, there is a lack of intention in adopting a roadmap for achieving the objectives and goals outlined in these documents and implementing them with determination. In this context, in order to achieve inclusive growth, it is crucial to internalize the issue in terms of not only action plans but also implementation.